Pengaruh Pelatihan Terhadap Produktivitas Karyawan di PT PLN Indonesia Power Unit Bisnis Pembangkitan Mahakam Melalui Komunikasi sebagai Variabel Mediasi - Helmalia Putri Syaiffudin; Vera Anitra; Rinda Sandayani Karhab (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the effect of training on employee productivity at PT PLN Indonesia Power Mahakam Generating Business Unit (UBP), with communication as a mediating variable. The background of this research is based on the importance of improving the quality of human resources through training as a key strategy to face the challenges of a dynamic electricity industry that demands high professionalism. Training is seen as a strategic investment that not only improves employee skills and productivity but also strengthens the company's competitiveness amid technological changes and evolving market needs. This research uses a quantitative method with a survey approach. Data were collected through questionnaires distributed to employees of PT PLN UBP Mahakam, with a total of 100 respondents. Data analysis was conducted using PLS-SEM techniques to test the relationship between training, communication, and employee productivity variables. The results showed that training has a positive and significant effect on employee productivity. In addition, communication is proven to significantly mediate the effect of training on productivity. This means that effective training not only increases individual competence, but also improves the quality of internal communication, which in turn has an impact on increasing overall productivity. This finding strengthens the evidence that training and communication are key factors in human resource development and achieving organizational goals. Based on the results of the study, it is recommended that companies continue to develop training programs that are relevant to job needs and strengthen internal communication systems